Analisis Kesalahan Dalam Menyelesaikan Soal Logaritma Pada Siswa Kelas X SMK N 1 Banyudono Tahun 2015/2016 - Setiyawan, Budi; , Dra. Sri Sutarni,M.Pd (2016)
This study aimed to analyze the errors and the causes errors of students in solving logarithms. This type of research is descriptive qualitative research design phenomenology. Respondents were students of class X SMK N 1 Banyudono. Data collection techniques used is a test, interview, and documentation. Data analysis techniques with methods of three paths: data reduction, data presentation, and conclusion. The validity of the data using methodological triangulation method tests, interviews and documentation. Based on the results the percentage of error analysis has been done can be concluded that the error per question most often do the students are (1) error count, (2) misconceptions, (3) the statistical error. To misconception about the number 1: 0%, No. 2: 34%, number 3: 18.75% and the number 4: 28.125. To miscalculation about the number 1: 0%, No. 2: 50%, Number 3: 37.5%, number 4: 43.75%. As for the statistical error number 1: 0%, No. 2: 12%, number 3: 18.75%, number 4: 28.125%. Judging from the results above show that the percentage of miscalculation that often do students. Percentage huge miscalculation performed by the students due to careless students in the count or less thorough in the end results. Keywords: Error Analysis , Mathematics , Material logarithm